Randomised controlled trial of effect of Baby Check on use of health services in first 6 months of life. Issue 7200 (26th June 1999) - Thomson, Hilary; Ross, Sue; Wilson, Philip; McConnachie, Alex; Watson, Richard
Abstract: Objective: To evaluate the effect of Baby Check, an illness scoring system for babies of 6 months or less, on parents' use of health services for their baby. Design: Randomised controlled trial. Setting: 13 general practices in Glasgow. Subjects: 997 newly delivered mothers, randomised to receive either Baby Check and Play It Safe, an accident prevention leaflet (n=497), or Play It Safe alone (control group, n=500). Main outcome measures: Data on consultations and referrals extracted from general practice notes after 6 months. Results: At the time of recruitment, maternal characteristics were similar for both groups (mean maternal age 29 years; deprivation categories 6 and 1 in both groups; 424 (45%) mothers were primiparous). At 6 months, general practice notes were available for 467 (94%) of the Baby Check group and 468 (94%) of the control group. The number of general practitioner consultations did not differ between the groups: median number of consultations was 2 (interquartile range 1 to 4) in the Baby Check group, and 2 (1 to 3) in the control group. Use of out of hours services did not differ significantly between the two groups (86 v 85; P=0.93). Conclusion: Distributing Baby Check to an unselected group of mothers does not affect use of health services for infants up to 6 months of age.